PENGARUH KOMPOS JERAMI PADI PLUS TITHONIA DAN BIOCHAR TERHADAP SIFAT KIMIA TANAH SAWAH - M. Lucky; Syafrimen Yasin; G Gusnidar (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
The low level of soil fertility resulted in a decrease in productivity intensification of rice fields. One of the efforts conducted by farmers to improve fertility is the continuous application of synthetic fertilizer (PS). Intensive use made PS cause pollution and soil damage. This study was aimed to identification at the best combination the straw plus tithonia compost (J+T) and biochar to improve soil chemical properties intensification of rice fields, and then looked the effect of increasing compost (J+T) and biochar to soil chemical properties intensification of rice fields. This research was conducted in rice fields in Kuranji, Padang City, West Sumatera. The experimental design used a randomized complete block design. The treatments were 0% compost (J+T) and 0% biochar; 100% compost (J+T); 75% compost (J+T) and 25% biochar; 50% compost (J+T) and 50% biochar; 25% compost (J+T) and 75% biochar; 100% biochar. The results showed that the 25% compost (J+T) and 75% biochar was the best combination to improve soil chemical properties intensification of rice fields. The dosage increased soil pH by 6.30; Eh 65.00 mV; organic C 2.53%; organic M 4.35%; total N 0.93%; available P 26.00 ppm; CEC 40,48 cmol kg-1; exchangeable K 1.47 cmol kg-1; exchangeable Ca 1.06 cmol kg-1; exchangeable Na 0.67 cmol kg-1; and exchangeable Mg 0.57 cmol kg-1.